NZ J Ecol 2017
DOI: 10.20417/nzjecol.41.9
|View full text |Cite
|
Sign up to set email alerts
|

Invasive rodents, an overlooked threat for skinks in a tropical island hotspot of biodiversity

Abstract: Squamata are one of the most threatened groups among island vertebrates, facing high pressure from exotic species. However, the contribution of small terrestrial reptiles in invasive rodents' diet remains poorly investigated, partly because of the lack of tools for accurately identifying chewed prey fragments in gut contents. The New Caledonia archipelago (South Pacific) hosts an exceptional terrestrial squamata fauna (105 species, 91.6% endemic) that are faced with many invasive species (rodents, feral cats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The ship rat is also an efficient colonizer of small islets, and once it reaches an archipelago, there is frequent inter-island dispersal (Cheylan, Granjon & -Davidian, 1998). Both its diet and dispersal capacity induced historical pernicious effects on island reptiles, particularly on isolated oceanic islands (Thibault et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The ship rat is also an efficient colonizer of small islets, and once it reaches an archipelago, there is frequent inter-island dispersal (Cheylan, Granjon & -Davidian, 1998). Both its diet and dispersal capacity induced historical pernicious effects on island reptiles, particularly on isolated oceanic islands (Thibault et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the management of invasive species in New Caledonia is of primary importance in order to preserve its native and endemic biodiversity (Beauvais et al, 2006, Pascal et al 2008, very few studies have been conducted on New Caledonia's rat population ecology and diet (Robinet et al 1998, Rouys 2008, Brescia 2011, Thibault et al 2017). Our study shows that both Rattus spp.…”
Section: Discussionmentioning
confidence: 99%
“…For both rat species, diets were assessed by morphological analysis of food items from stomach and caecum contents. Although the majority of diet studies are based on stomach contents alone (Sugihara 1997), a recent study has shown that combined analysis of stomach and caecum contents provides much more information on taxon richness in rat diet, particularly for Squamata (Thibault et al 2017). Each sample, that is, stomach or caecum, was rinsed with tap water and sieved through a 500 mm mesh (Sugihara 1997).…”
Section: Rat Diet Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…come from the presence of invasive species, primarily rodents (Pacific Rat and Ship Rat), feral cats, and invasive ants. The negative impact of rats on island lizard populations has been well documented (Whitaker 1973;Monks et al 2014), with their presence clearly suppressing potential lizard population densities (Thibault et al 2017). A negative impact on lizard populations by the Little Red Fire Ant (LFA) Wasmannia auropunctata has also been identified, with studies in dry forest habitat in New Caledonia reporting a lower abundance of several lizard species in invaded areas (Jourdan et al 2001), and it is considered to be a major threat islandwide.…”
Section: Systematicsmentioning
confidence: 99%